1990
DOI: 10.1093/jnci/82.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alfa-2a Combined With Phototherapy in the Treatment of Cutaneous T-Cell Lymphoma

Abstract: Escalating doses of recombinant interferon alfa-2a (Roferon-A), administered intramuscularly three times weekly, combined with psoralen plus ultraviolet light irradiation (PUVA), were tested in a phase I trial for the therapy of patients with cutaneous T-cell lymphomas (CTCL). Interferon doses were escalated in groups of three patients from 6 million to 30 million IUs three times weekly. Disease stages ranged from IB to IVB. Eighty percent of the patients entered in this trial had failed at least one prior the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…Psoralens and ultraviolet A are usually well tolerated, although interferon is limited by side effects related to the dose 2. Like Mostow et al,4 however, we found that a regimen of low dose interferon was extremely well tolerated, even by an 89 year old woman.…”
supporting
confidence: 70%
“…Psoralens and ultraviolet A are usually well tolerated, although interferon is limited by side effects related to the dose 2. Like Mostow et al,4 however, we found that a regimen of low dose interferon was extremely well tolerated, even by an 89 year old woman.…”
supporting
confidence: 70%
“…61,67 Interferon alfa in combination with psoralen plus ultraviolet (UV) A (PUVA) has shown efficacy in E-MF (blood involvement unspecified) 56,68-70 but there was not been a uniform response in the two patients with SS reported. 71,72 Interferon in combination with retinoids (isotretinoin, etretinate, bexarotene) has been noted to be effective in late-stage MF/SS 73-77 but, to our knowledge, there are no studies where the combination is compared with monotherapy alone and none where the results in SS are specifically addressed. Patients with SS treated with a combination of interferon alfa and pentostatin 78 or interferon alfa and fludarabine 79 demonstrated ORs but the overall response rate (RR) in all patients with MF thus treated (41% and 51%, respectively) was not higher than that seen in other studies with interferon alone.…”
Section: Interferon Alfamentioning
confidence: 99%
“…Responses, which may be achieved within a few months, are observed in patients with tumor-stage MF and SS. Furthermore, interferon-alpha may be successfully combined with a number of other therapeutic modalities, including PUVA, bexarotene, chemotherapy and ECP, which are frequently utilized in the management of these patients [289][290][291][292][293][294][295][296][297][298][299][300][301][302]. For example, in a cohort of 51 patients (42 of which had advancedstage disease) treated with single-agent, low-dose, interferon-alpha, responses were observed in 34 (67%), 21 (41%) of which were complete and maintained long-term in nine patients [288].…”
Section: Interferon-alphamentioning
confidence: 99%